Students' Perceptions In Interpersonal Communication About Deactivating The Blue Check And Last Seen Of Whatsapp Application - Intan Ertika; Yanto Yanto; Bayu Risdiyanto (Penerbit Jurnal Indonesia, 2024)
This study aims to determine students’ perceptions about the deactivation of the blue check and Last Seen WhatsApp application. Testing in this study used qualitative methods. The informants in this study were students at Dehasen University of Communication Science Study Program. The informant selection technique used purposive sampling. The analysis used is qualitative analysis in the form of a collection of tangible words consisting of three streams of activities that occur simultaneously, namely data reduction, data presentation, and conclusion drawing / verification. The results showed that disabling blue check and Last Seen did not make them feel objected and disturbed by disabling blue check and Last Seen. From disabling blue check and Last Seen, it is hoped that it can give themselves more time to reply to messages on WhatsApp, but disabling blue check and Last Seen which shows the negative side of themselves is still considered arrogant for people who are not used to it.